Meta-Analysis: Seasonal Variations in pH Concentration and Their Impact on River Water Quality - Oktaviani, Eva; Marpaung, Sutan Sahala Muda; Kurniawan, Hendra; Syah, Firman; Hendra Kurniawan (Jurnal Biologi Tropis, 2025)
Water is a vital resource, yet its quality is increasingly affected by climate change and human activities. Seasonal variations, particularly between dry and rainy periods, may influence river water quality, with pH serving as a key chemical parameter. This study aimed to examine the effect of seasonal differences on river water pH levels using meta-analysis. The objective was to provide evidence of whether rainfall patterns significantly alter pH concentrations in tropical and subtropical regions. Relevant literature was collected from online databases using keywords such as “water pollution,” “dry season,” and “wet season.” Out of more than 40 studies, four articles with complete seasonal pH data were selected. Data were processed using OpenMEE software with a random-effects model, and the log response ratio (lnRR) was applied to compare pH values between dry (control) and rainy (treatment) seasons. The analysis revealed no significant seasonal differences in pH levels. The overall effect size was weak (–0.758), with the 95% confidence interval crossing zero. Heterogeneity among studies was high (I² = 80.325%), yet subgroup analyses by region, climate, and location confirmed consistent results. In conclusion, river water pH in tropical and subtropical areas remains relatively stable across seasons, influenced by steady climate conditions, well-mixed water bodies, and consistent vegetation. Broader datasets, especially from Indonesia, are needed to validate these findings.